Cationic indium catalysts for ring opening polymerization: tuning reactivity with hemilabile ligands. Issue 25 (22nd April 2020) - Goonesinghe, Chatura; Roshandel, Hootan; Diaz, Carlos; Jung, Hyuk-Joon; Nyamayaro, Kudzanai; Ezhova, Maria; Mehrkhodavandi, Parisa
Abstract : This is an in-depth study into the role hemilabile ligands play in tuning stability and reactivity in cationic indium complexes. Abstract : This is a comprehensive study of the effects of rationally designed hemilabile ligands on the stability, reactivity, and change in catalytic behavior of indium complexes. We report cationic alkyl indium complexes supported by a family of hemi-salen type ligands bearing hemilabile thiophenyl (2a ), furfuryl (2b ) and pyridyl (2c ) pendant donor arms. Shelf-life and stability of these complexes followed the trend 2a < 2b < 2c, showing direct correlation to the affinity of the pendant donor group to the indium center. Reactivity towards polymerization of epichlorohydrin and cyclohexene oxide followed the trend 2a > 2b > 2c with control of polymerization following an inverse relationship to reactivity. Surprisingly, 2c polymerized racemic lactide without an external initiator, likely through an alkyl-initiated coordination-insertion mechanism.